Redox regulation of signal transduction: tyrosine phosphorylation and calcium influx. - Staal, F J (1994)
Studies presented here show that altering the intracellular redox balance by decreasing glutathione levels profoundly affects early signal transduction events in human T cells. In a T-cell receptor (TCR) signaling model, short-term pretreatment with buthionine sulfoximine, which specifically decreases intracellular glutathione, essentially abrogates the stimulation of calcium influx by anti-CD3 antibodies without significantly impairing other aspects of TCR-initiated signal transduction, such as overall levels of TCR-stimulated tyrosine phosphorylation. In an inflammatory-cytokine signaling model, the failure of tumor necrosis factor alpha to stimulate more than minimal tyrosine phosphorylation in lymphocytes is overcome by buthionine sulfoximine pretreatment--i.e., tumor necrosis factor alpha stimulates extensive tyrosine phosphorylation in glutathione-depleted lymphocytes. These redox-dependent changes in T-cell responsiveness suggest that the glutathione deficiency that we and others have demonstrated in human immunodeficiency virus-infected individuals may contribute significantly to the immunodeficiency and the increased inflammatory reactions in these individuals.